Pengenalan Keberlanjutan Usaha dengan Perhitungan HPP yang Wajar pada Pelaku UMKM di Desa Pagedangan - Irawati, Wiwit; Ersyafdi, Ilham Ramadhan; Ginting, Rafles; Puspitasari, Ayu; Rumaizha, Riri; Harry Mukti, Aloysius; Marpaung, Oktavia; Swasti Putri, Ika (Ikatan Cendekiawan Muda Akuntansi, 2023)
Calculating a reasonable Cost of Goods Sold (COGS) is very important for Micro, Small and Medium Enterprises (MSMEs) because it has a direct effect on the profitability and sustainability of the business. However, in practice there are still many MSME entities that have not calculated their COGS in accordance with accounting methods in accordance with the correct EMKM Financial Accounting Standards (SAK), this is partly due to limited MSME resources so that COGS calculations are inaccurate. Based on this background, service lecturers from various universities and affiliated with the professional organization, namely ICMA, collaborated to provide Community Service in the form of introducing business sustainability with reasonable COGS calculations targeting MSMEs in Pagedangan Village. Armed with basic accounting knowledge, especially reasonable COGS calculations, it is hoped that Pagedangan Village MSMEs can develop their businesses and open up opportunities to progress in the future.